A Program to Support Scholarship During Internal Medicine Residency Training: Impact on Academic Productivity and Resident Experiences. Issue 5 (20th October 2019) - Carter, Andrea E.; Anderson, Timothy S.; Rodriguez, Keri L.; Hruska, Kristina L.; Zimmer, Shanta M.; Spagnoletti, Carla L.; Morris, Alison; Kapoor, Wishwa N.; Fine, Michael J.
Abstract: Problem: Although scholarship during residency training is an important requirement from the Accreditation Council for Graduate Medical Education, efforts to support resident scholarship have demonstrated inconsistent effects and have not comprehensively evaluated resident experiences. Intervention: We developed the Leadership and Discovery Program (LEAD) to facilitate scholarship among all non-research-track categorical internal medicine (IM) residents. This multifaceted program set expectations for all residents to participate in a scholarly project, supported faculty to manage the program, facilitated access to faculty mentors, established a local resident research day to highlight scholarship, and developed a didactic lecture series. Context: We implemented LEAD at a large university training program. We assessed resident scholarship before and after LEAD implementation using objective metrics of academic productivity (i.e., scientific presentations, peer-reviewed publications, and both presentations and publications). We compared these metrics in LEAD participants and a similar historical group of pre-LEAD controls. We also assessed these outcomes over the same two periods in research track residents who participated in research training independent from and predating LEAD (research track controls and pre-LEAD research track controls). We conducted focus groups to qualitatively assess resident experiences with LEAD. Outcome: Compared to 63 pre-LEAD controls, greater proportions of 52 LEAD participants completed scientific presentations (48.1% vs. 28.6%, p  = .03) and scientific presentations and peer-reviewed publications (23.1% vs. 9.5%, p  = .05). No significant differences existed for any academic productivity metrics among research track controls and pre-LEAD research track controls ( p  > .23, all comparisons). Perceived facilitators of participation in LEAD included residents' desire for research experiences and opportunities to publish prior to fellowship training; the main barrier to participation was feeling overwhelmed due to the time constraints imposed by clinical training. Suggestions for improvement included establishing clearer programmatic expectations and providing lists of potential mentors and projects. Lessons Learned: Implementation of a multifaceted program to support scholarship during residency was associated with significant increases in academic productivity among IM residents. Residents perceived that programs to support scholarship during residency training should outline clear expectations and identify available mentors and projects for residents who are challenged by the time constraints of clinical training.